Resolving Forest and Land Fires (KARHUTLA) in Indonesia through "Jalan Pantas" or "Jalan Pintas"? - Gunawan, Desri (Law Research Review Quarterly, 2016)
This research aims to dissect the way to solve land burning in Indonesia through "proper roads" which is a way that is in accordance with procedures or through "shortcuts" which is a direct way to the core problem. The scope of this writing covers legal, political, economic and socio-cultural aspects. The method used is descriptive analysis with the perspective of a rule of law that emphasizes sovereignty based on Pancasila, specifically the 5th precept, namely social justice for all the people of Indonesia. The results of this study indicate that land burning is mostly carried out by companies rather than the community. This continues because of the weak application of the law, both because of the limited resources of law enforcement officials and long and long-winded procedures. Cost efficiency factors are the main reason for burning and the view of burning land is common and has been done for generations. Settlement through the "proper way" by firmly enforcing the existing rules, Giving a deterrent effect to the perpetrators of forest fires through administrative, civil, criminal and disciplinary sanctions. Completion of "short cut" with a preventive approach (preventive) and non-court (non litigation). The conclusion of this paper is that each path has rationalization, consequences and benefits. The choice of road is an agreement from the executive, legislative and judiciary at the state, provincial and district levels.